To solve the equation \( 12 = bY - 3 \) for \( Y \), we will perform the following steps, identifying the properties used in each step.
-
Add 3 to both sides of the equation.
\[ 12 + 3 = bY - 3 + 3 \]
Using the Addition Property of Equality, we maintain the equality by adding the same value (3) to both sides.
\[ 15 = bY \]
-
Now, divide both sides by \( b \) to isolate \( Y \).
\[ \frac{15}{b} = \frac{bY}{b} \]
Using the Division Property of Equality, we maintain the equality by dividing both sides by the same non-zero number (assuming \( b \neq 0 \)).
\[ \frac{15}{b} = Y \]
-
Rearranging, we write the solution.
\[ Y = \frac{15}{b} \]
Thus, the solution for \( Y \) is:
\[ Y = \frac{15}{b} \]
In summary, we used the Addition Property of Equality in step 1 and the Division Property of Equality in step 2 to isolate \( Y \).